Ionotropic receptor-dependent moist and dry cells control hygrosensation in Drosophila - Knecht, Z; Silbering, A; Cruz, J; Yang, L; Croset, V; Benton, R; Garrity, P (eLife Sciences, 2017)
Insects use hygrosensation (humidity sensing) to avoid desiccation and, in vectors such as mosquitoes, to locate vertebrate hosts. Sensory neurons activated by either dry or moist air ('dry cells' and 'moist cells') have been described in many insects, but their behavioral roles and the molecular basis of their hygrosensitivity remain unclear. We recently reported that Drosophila hygrosensation relies on three Ionotropic Receptors (IRs) required for dry cell function: IR25a, IR93a and IR40a (Knecht et al., 2016). Here, we discover Drosophila moist cells and show that they require IR25a and IR93a together with IR68a, a conserved, but orphan IR. Both IR68a- and IR40a-dependent pathways drive hygrosensory behavior: each is important for dry-seeking by hydrated flies and together they underlie moist-seeking by dehydrated flies. These studies reveal that humidity sensing in Drosophila, and likely other insects, involves the combined activity of two molecularly related but neuronally distinct hygrosensing systems.